Actions are characterized by ‘canonical moments’ in a sequence of movements - Brady, Nuala; Gough, Patricia; Leonard, Sophie; Allan, Paul; McManus, Caoimhe; Foley, Tomas; O'Leary, Aoife; McGovern, David P. (Cognition, 2024)
Understanding what others are doing is an essential aspect of social cognition that depends on our ability to quickly recognize and categorize their actions. To effectively study action recognition we need to understand how actions are bounded, where they start and where they end. Here we borrow a conceptual approach – the notion of ‘canonicality' – introduced by Palmer and colleagues in their study of object recognition and apply it to the study of action recognition. Using a set of 50 video clips sourced from stock photography sites, we show that many everyday actions – transitive and intransitive, social and non-social, communicative – are characterized by ‘canonical moments' in a sequence of movements that are agreed by participants to ‘best represent’ a named action, as indicated in a forced choice (Exp 1, n = 142) and a free choice (Exp 2, n = 125) paradigm. In Exp 3 (n = 102) we confirm that canonical moments from action sequences are more readily named as depicting specific actions and, mirroring research in object recognition, that such canonical moments are privileged in memory (Exp 4, n = 95). We suggest that ‘canonical moments', being those that convey maximal information about human actions, are integral to the representation of human action.11This research was first presented at the European Conference on Visual Perception (Brady et al., 2021).